(untitled) (Actual Problems of Psychology in Educational Institutions, 2021)
The article is devoted to the analysis of the phenomenon of pedagogical creativity as one of the basic determinants of the creative development of the individual. Various psychological and pedagogical ideas concerning the essence, content and specifics of pedagogical creativity are considered. The article describes the structure and main stages of creativity implementation in the pedagogical process. The article asserts the presence of algorithmic and creative components in pedagogical creativity, which makes it possible to master creativity both at the objective and subjective levels.